Vitamin D and hippocampal development-the story so far - Lardner, Anne L. (Frontiers in Molecular Neuroscience, 2015)
Epidemiological studies suggest that vitamin D insufficiency may be prevalent in young as well as older populations. The pleiotropic effects of vitamin D are now beyond dispute and a growing number of studies provide accumulating evidence of a role for vitamin D in brain development and function. A number of studies to date have investigated the effects of early-life vitamin D deprivation on adult hippocampus in animals and humans, and there is a growing body of evidence to suggest a role for this hormone in the development of selected hippocampal functions such as latent inhibition and hole board habituation in rats. There are few studies to date of vitamin D deprivation or supplementation on early hippocampal development in vivo. However, a small number of studies, mostly in vitro, point to a role for vitamin D in differentiation and development of hippocampal neurons. There is also limited evidence that supplementation with vitamin D following a period of deprivation is capable of restoring cellular activity and later function. Further avenues of future research are outlined including animal studies on the effects of vitamin D deprivation and inadequacy on early hippocampal biochemistry and function e.g. measurement of BDNF levels, GABAergic activity, long-term potentiation and spatial navigation,. It also remains to be established if there are critical developmental windows during which vitamin D is required. In light of the importance of the hippocampus in LTP and spatial learning, further investigations on the early effects of vitamin D deprivation on hippocampal development are warranted